IMPLEMENTASI RPG MAKER MV PADA GAME RPG TOWER OF ETERNITY - Muhammad Fauzhan Nasril; Yuli Maharetta Arianti; Nani Mintarsih (Asosiasi Dosen Muda Indonesia, 2023)
The development of technology has brought about changes in various aspects of human life, one of which is the entertainment media, namely video games. Video games are a common form of entertainment that typically follows certain rules, providing opportunities for achieving victory. Video games encompass various genres, one of which is RPG (Role-Playing Game), which usually emphasizes gameplay, story, and characters. The game